Livelihood impacts of water policy changes: Evidence from a coastal area of the Mekong River Delta - Hoanh, Chu Thai; To Phuc Tuong; Gallop, K.M.; Gowing, J.W.; Kam, Suan Pheng; Khiem, N.T.; Phong, N.D. (2003)
The coastal zone of the Mekong River delta has experienced rapid economic and environmental change during the last decade. Given the nature of the environment and the level of dependence on the natural resource base, policies for land and water were very influential in this process. The emphasis on rice created an imperative to control saline intrusion, which was realized through construction of major engineering works over an extended period (1994-2000). The inertia built up by this process led to a divergence between policy and practice, and adversely affected the livelihoods of fishers and of those farmers who live on aquaculture. This prompted the government to re-think about the rice-focus policy, in favor of a land and water policy for balanced rice and aquaculture production. The paper describes an analytical process, which was adopted to explore the feasibility of adopting the new policy for balanced development of both rice and shrimp production and discusses the impact of the new policy on farmers' livelihoods.